Mental Health Stressors in Higher Education Instructors and Students in Mexico During the Emergency Remote Teaching Implementation due to COVID-19 - Zapata-Garibay, Rogelio; González-Fagoaga, Jesús Eduardo; Asadi-González, Ahmed Ali; Martínez-Alvarado, Julio Román; Chavez-Baray, Silvia M.; Plascencia-López, Ismael; González-Fagoaga, Clara Judith (Frontiers in Education, 2021)
The COVID 19 pandemic has had a significant impact on the physical and emotional health of the population. In the case of specific populations such as students and instructors, the change in the teaching-learning model has required both groups to adapt to online learning platforms and modify all academic activities in the context of implementing the emergency remote education model. The relevance of mental health has been continually neglected; however, due to the COVID-19 epidemiological outbreak, the impact of confinement on populations' mental health has been incorporated into public discussion. In particular, the health emergency's impact on health workers in the first line of care has been highlighted. However, the effect of mental health on the locked-down population and those who are encouraged to work from home, a group in which university professors and students are located, has been emphasized. To understand the changes faced by higher education instructors and students, derived from the implementation of the emergency remote teaching model in the context of the pandemic by COVID-19, we developed a study to investigate the experiences of this sector, with particular emphasis on the mental health stressors associated with their academic activities. We examined indicators related to anxiety, depression, motivation-demotivation, coping, and contextual and family conditions that could generate stress in the teaching-learning process during the emergency remote teaching model. This study recruited a sample of 1,040 participants (380 instructors and 660 students) from more than 97 universities and 118 academic programs across the country. As a result, we have found that teachers have faced less difficulty with the teaching-learning model's changes and how they deal with confinement. Similarly, this study has identified that women in general, both instructors and students, have more significant signs and symptoms related to mental health conditions, while men, both instructors, and students, resent the lack of socialization in the work and study centers.